Sentiment Analysis of Presidential Candidates in 2024: A Comparison of the Performance of Support Vector Machine and Random Forest with N-Gram Method - Muhammad Rizki Ramadhan; Kholiq Budiman (Universitas Negeri Semarang, 2025)
Abstract. This paper conducts a sentiment analysis of presidential candidates in Indonesia's 2024 election using Twitter data. Utilizing the